External Conditions, Internal Rationality: Spinoza on the Rationality of Suicide - Ian MacLean-Evans (Journal of Spinoza Studies, 2023)
I argue alongside some other scholars that there is a plausible reading of Spinoza’s philosophy of suicide which holds both of the following tenets: first, that suicides occur because of external conditions, and second, that there are at least some suicides which are rational. These two tenets require special attention because they seem to be the source of significant tension. For Spinoza, if one’s cognitions are to be the most adequate, they must be “disposed internally” (E2p29s/G II 114), or determined more from one’s own mental nature than from “fortuitous encounters” with other things (E2p29s/G II 114). It may seem there is a conflict, then, in saying both that there are rational suicides in the Spinozist framework, and that suicides must always be a result of external conditions: it seems a suicide simply cannot be rational if it is the result of external conditions. But this tension, it will be shown, can be dissolved. Once this tension is dealt with, I offer some brief closing arguments. I explain how this reading of Spinoza’s philosophy of suicide can satisfy a call for new suicide research which avoids forms of over-individualism and epistemic injustice, and which encourages us to abolish oppressive conditions that lead to rational suicides.